2019
DOI: 10.3389/fonc.2019.00482
|View full text |Cite
|
Sign up to set email alerts
|

Laser Capture Microdissection and RNA-Seq Analysis: High Sensitivity Approaches to Explain Histopathological Heterogeneity in Human Glioblastoma FFPE Archived Tissues

Abstract: Laser capture microdissection (LCM) coupled with RNA-seq is a powerful tool to identify genes that are differentially expressed in specific histological tumor subtypes. To better understand the role of single tumor cell populations in the complex heterogeneity of glioblastoma, we paired microdissection and NGS technology to study intra-tumoral differences into specific histological regions and cells of human GBM FFPE tumors. We here isolated astrocytes, neurons and endothelial cells in 6 different histological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 77 publications
2
47
0
Order By: Relevance
“…Interestingly, our results suggest that some conventional antipsychotics among drugs mentioned above, including amitriptyline, fluoxetine, and imipramine, may also play a surprising role in the treatment of GBM, which is consistent with previous studies and offers new hope for patients with GBM (12,75,76,80,83,84,104). In addition, Leite et al (105) demonstrated that clomipramine (tricyclic antidepressant drugs such as imipramine) has an impact on GBM growth and has no toxicity in normal cells (astrocytes and microglia).…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, our results suggest that some conventional antipsychotics among drugs mentioned above, including amitriptyline, fluoxetine, and imipramine, may also play a surprising role in the treatment of GBM, which is consistent with previous studies and offers new hope for patients with GBM (12,75,76,80,83,84,104). In addition, Leite et al (105) demonstrated that clomipramine (tricyclic antidepressant drugs such as imipramine) has an impact on GBM growth and has no toxicity in normal cells (astrocytes and microglia).…”
Section: Discussionsupporting
confidence: 90%
“…RNA-seq has been widely used in addressing various biological questions, from exploring the pathogenesis of disease (1,2) to constructing transcriptome maps for various species (3,4). RNA-seq provides informative assessments of samples, especially when heterogeneity in a complex biological system (5,6) or time-dependent dynamic processes are being investigated (7)(8)(9). A typical RNA-seq experiment requires a DNA library generated from messenger RNA (mRNA) transcripts.…”
mentioning
confidence: 99%
“…These overexpressed genes and pathways were known to promote cell survival and infiltrative growth, migration, and resistance to cancer-targeted therapies in GBM. Civita et al (32) also observed a considerable up-regulation of growth factors signaling pathways in pseudopalisading cells compared to the tumor core. The data demonstrate that certain molecular events are region specific and different regions are molecularly interrelated.…”
Section: Laser Capture Micro-dissected Rnaseqmentioning
confidence: 91%
“…The study established initial feasibility of LCM-RNASeq in a six patient sample population with an aim to identify biomarkers for lung cancer progression. Several studies have recently emerged, here we provide one example that highlights how LCM-RNAseq data can be used to deconvolve multiple cell type-specific gene expression profiles in cancer (32). In this study, the expression profiles of six specific tissue compartments of human glioblastoma (BGM) were analyzed using LCM-RNAseq techniques.…”
Section: Laser Capture Micro-dissected Rnaseqmentioning
confidence: 99%